The Influence of Workload on Burnout of Nurses at Sele Be Solu Provincial General Hospital, Sorong City During the Period of Endemic Transition of Covid-19 Through Role Stress as a Mediator - Mufti, Digor; Edwar, Rizka Cintya; Ridwan, Akmal; Noormiati (Jurnal Manajemen Bisnis, 2024)
This study aims to analyze the influence of workload on nurse burnout at the Sele Be Solu Regional General Hospital, Sorong City during the transition period of the endemic Covid-19 through role stress as an intermediary. This research uses quantitative methods. The population in this study is all the nurses at the Sele Be Solu Regional General Hospital, Bandar Sorong, totaling 133 nurses. The number of samples was calculated using the Slovin formula with an error tolerance of 5℅, thus obtaining a sample size of 100 nurses. Data collection was carried out using a questionnaire, then the data was processed using the SEM PLS program. The results of the research show that workload has a positive and significant effect on burnout of Nurses at the Sele Be Solu Regional General Hospital Sorong City, workload has a positive and significant effect on role stress for Nurses at the Sele Be Solu Regional General Hospital Sorong City, and role stress has a positive and significant effect. on the burnout of Nurses at the Sele Be Solu Regional General Hospital Sorong City, and role stress has a positive and significant influence on the influence of workload on the burnout of Nurses at the Sele Be Solu Regional General Hospital Sorong City.